Menstrual cycle phase-based strength & conditioning training for elite team sport female athletes - Moore, S. R.; Bruinvels, G.; Smith-Ryan, A. E. (Strength and Conditioning Journal, 2025)
Despite continued success, female athletes are still underresourced and minoritized in research and applied spaces. This has translated to disparate injury and health outcomes among female athletes resulting from a sport infrastructure built on male physiology. The purpose of this article is to propose an evidence- and experience-based menstrual cycle (MC) phase-based training model for practitioners working with elite female athletes in team sport. Here, we provide physiological rationale, privacy considerations, and best practices to support female-centric training. The following model proposes periodization based on a theorized capacity of adaptation rather than acute performance or symptomology alone because evidence suggests that performance changes across the MC may be highly individual. In addition, strength and conditioning programs are formulated to balance stressors and recovery in the pursuit of optimal adaptation, irrelevant of acute exercise performance. Finally, we identify future directions for applied practitioners and researchers, and the potential need for collaborative innovations between the communities. Creating a training model based on the physiology and experience of female athletes communicates to female athletes that they belong in sport and are worthy of our time, attention, and resources to improve their health, safety, and performance now and through active retirement.